Reflection of Brand Oil prices in the electricity index and BIST 100 index in Türkiye - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2025)
Investigating the relationship between changes in oil prices and individual stock prices can be useful in making more conscious decisions in financial markets, managing risks and better understanding economic developments. The aim of this study is to reveal how these changes affect the indices when oil prices, BIST 100 index and BIST electricity index change. For this purpose, BIST 100, BIST electricity index and oil price changes were subjected to Granger analysis in the time period of 19.06.2014-19.06.2024. The obtained result reveals that there is a significant two-way relationship between BIST 100 index and BIST electricity index. On the other hand, no relationship was found between oil prices and the other two indices.